Effects of different post-harvest treatments on bio-chemical characters and diseases of litchi in storage - Uddin Talukder, Fakhar; Sohanur Rahman, Md.; Kamrul Hassan, Md. (International Journal of Advanced Geosciences, 2020)
Objective of the study was to evaluate the effects of different post-harvest treatments on bio-chemical characters and diseases of litchi (Litchi chinensis Sonn, var. Bombai). The experiment consisted of two factors. Factor A: Temperature viz. T1: Ambient temperature, T2: 4ºC temperature; Factor B: PP bags (Polypropylene bag) viz. P1: Control (unwrapped), P2: 50 micro meter (µm) PP bag, P3: 75µmm PP bag, P4: 100µm PP bag. The experiment was conducted in completely randomized design (CRD) with three replications. Significant variation was observed in total soluble solid, PH of fruit pulp, vitamin c content, percent disease incidence and disease severity during the storage period. TSS contents increased up to the 6th day of storage and there after declined. pH values were maximum (4.14) in the fruits kept in 100µ polypropylene bag at ambient temperature. Vitamin C continent decreased with the increase of storage period. Disease incidence and severity progress with the storage period. Among the treated and untreated fruits, 75µm pp bag at low temperature (4ºC) treatment exhibited better storage performance. More research should be conducted by using other litchi cultivar like Bedana, China-3 etc. Various technologies have been devised to minimize the post-harvest losses of litchi, one of such technologies is the use of PP bag & low temperature.